O ENSINO DAS LUTAS NAS AULAS DE EDUCÇÃO FÍSICA: ANÁLISE DA PRÁTICA PEDAGÓGICA À LUZ DE ESPECIALISTAS - Rufino, Luiz Gustavo Bonatto; Darido, Suraya Cristina (Universidade Estadual de Maringá, 2015)
This study aimed to analyze college teachers' opinions experts in fight contents about the pedagogical practice in school Physical Education, proposing implications for the development of teacher education contexts. The sample consisted of 5 teachers selected intentionally, who participated in a semi-structured interview from a script previously built. Data analysis was performed using the content analysis technique, culminating with the inference of two categories: 1) restrictive factors, which seeks to analyze the main elements related to the development of fights contents in school; 2) possibilities, which accounted for proposals for building the fights ahead to today's social demands. We concluded that the pedagogical practice of fights in school presents some dilemmas arising from the way they are developed in teacher education, which requires changes that may value them as manifestations of body culture.

Objetivou-se analisar as opiniões de docentes universitários especialistas no tema das lutas sobre a prática pedagógica nas aulas de Educação Física na escola, propondo implicações para o desenvolvimento dos contextos de formação de professores. A amostra foi constituída por 5 professores selecionados de modo intencional que participaram de entrevistas semiestruturadas a partir de um roteiro previamente construído. A análise dos dados foi realizada por meio da técnica da análise de conteúdo, culminando com a inferência de duas categorias: 1) fatores restritivos, a qual buscou analisar os principais elementos de dificuldade no que corresponde ao desenvolvimento das lutas na escola; 2) possibilidades, a qual representou propostas de edificação das lutas frente às demandas sociais atuais. Conclui-se que a prática pedagógica das lutas na escola apresenta alguns dilemas oriundos da forma como elas são desenvolvidas no âmbito da formação, indicando a necessidade de alterações que possam valorizá-las como manifestações da cultura corporal.
THE TEACHING OF FIGHTS IN PHYSICAL EDUCATION CLASSES: ANALYZE OF PEDAGOGICAL PRACTICE IN THE LIGHT OF EXPERTS
Keywords: Professional Training; Teaching; Martial Arts; Capacitação Profissional; Ensino; Artes Marciais